A comment on Herzog, Baron, and Gibbons (2022) - Haley Daarstad; RyuGyung Park; Timea Balogh (Institute for Replication (I4R), 2023)
Herzog, Baron, and Gibbons (2022) explore the effects of exposure to official elite rhetoric and group cues on public support against the international nuclear weapons prohibition norm. The authors find that elite cues, in particular security and institutional cues, increase individuals' opposition to the Treaty on the Prohibition of Nuclear Weapons (TPNW). However, elite cues do not seem to have an effect on changing individuals' broader attitudes towards nuclear weapons, as measured by individuals' existing opposition to nuclear arms. We replicate and expand the authors' methods and results to test the robustness of the effects found in the study. First, we reproduce the main finding using the authors' original data and method. We do not find any coding errors that undermine the authors' analysis or conclusions. Second, we test the robustness of the results by (1) using a different operationalization of party identity, and (2) calculating additional subgroup analysis for gender. We find no significant differences between our replicated and the original results, however females' support for the TPNW is more responsive to security cues, while males' support is more responsive to institutions cues.
Additional information: This paper received a response: Herzog, Stephen, Jonathon Baron, and Rebecca Davis Gibbons. Gender Analysis and the Treaty on the Prohibition of Nuclear Weapons: A Response to Daarstad, Park, and Balogh. I4R Discussion Paper Series No. 98. Institute for Replication.
Keywords: 330